2004
DOI: 10.1074/jbc.m400680200
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-stimulated Endocytosis Controls Activity of the Mouse ZIP1 and ZIP3 Zinc Uptake Transporters

Abstract: The mouse mZip1 and mZip3 zinc transporters have been implicated in zinc acquisition by the cells of many tissues. This hypothesis raised the question of whether activity of these proteins is regulated to maintain zinc homeostasis. Neither mZIP1 nor mZIP3 mRNA levels are highly regulated by zinc status. Therefore, we investigated whether zinc controls the activity of these proteins post-translationally by altering their subcellular distribution. When expressed in transfected cells grown in zinc-replete medium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
111
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 29 publications
7
111
0
Order By: Relevance
“…Nonetheless, the subcellular distribution of mZip4-HA and mZip5-HA was assessed by immunofluorescence confocal microscopy to provide the foundation for studies of zinc-stimulated endocytosis in HEK293 cells. This same approach was used previously to show zinc-stimulated endocytosis of mZip1, mZip3, mZip4, and hZip4 (23,28). Cells were grown in a zinc-replete basal medium and then fixed, permeabilized, incubated with anti-HA antibody, and subsequently incubated with a fluorophore-conjugated secondary antibody.…”
Section: The Mzip5 Basolateral Zinc Transportermentioning
confidence: 99%
See 3 more Smart Citations
“…Nonetheless, the subcellular distribution of mZip4-HA and mZip5-HA was assessed by immunofluorescence confocal microscopy to provide the foundation for studies of zinc-stimulated endocytosis in HEK293 cells. This same approach was used previously to show zinc-stimulated endocytosis of mZip1, mZip3, mZip4, and hZip4 (23,28). Cells were grown in a zinc-replete basal medium and then fixed, permeabilized, incubated with anti-HA antibody, and subsequently incubated with a fluorophore-conjugated secondary antibody.…”
Section: The Mzip5 Basolateral Zinc Transportermentioning
confidence: 99%
“…For example, we have shown that several mammalian ZIP proteins are down-regulated by zinc post-translationally. Endocytosis of mZip1, mZip3, and mZip4 is stimulated by zinc thereby decreasing plasma membrane protein levels and reducing zinc uptake activity (23,28). To assess whether mZip5 is similarly regulated by zinc-stimulated endocytosis, we first examined mZip5-HA distribution in stably transfected HEK293 cells.…”
Section: Similarity Between Mammalian Zip4 and Zip5 Proteins And Theimentioning
confidence: 99%
See 2 more Smart Citations
“…For example, zinc exposure ubiquitinates and degrades the yeast zinc uptake transporter ZRT1 (23). Similarly, ZIP4 is quickly ubiquitinated and degraded in response to high zinc levels (47), suggesting that ubiquitination and degradation of zinc transporters may be a critical regulatory mechanism controlling zinc homeostasis. To our knowledge, our study is the first to identify a ubiquitin-mediated mechanism that is responsible for transiently increasing zinc efflux, contributing to our general understanding of zinc regulation.…”
Section: Discussionmentioning
confidence: 99%